Organizational Factors and Job Satisfaction: A Path Analysis Study: Pengaruh Faktor Organisasi terhadap Kepuasan Kerja: Studi Analisis Jalur - Della Savira Lazuardini; Hasan Ubaidillah (Academia Open, 2022)
This quantitative research study investigates the influence of organizational culture, leadership style, and work environment on job satisfaction, with organizational commitment as an intervening variable. The study population comprised 185 employees from a private organization, and a sample of 65 respondents was selected. A Likert scale questionnaire was employed for data collection. Utilizing path analysis techniques and t-statistic tests through SmartPLS 3 for Windows, the results revealed several significant findings. Firstly, organizational culture, leadership style, and work environment were found to have direct and positive effects on job satisfaction. Additionally, organizational culture and leadership style had direct and positive effects on job satisfaction through the mediating role of organizational commitment. Moreover, work environment indirectly influenced job satisfaction through organizational commitment. Lastly, organizational commitment was found to have a direct and positive impact on job satisfaction. These findings highlight the significance of fostering a positive organizational culture, effective leadership, and a conducive work environment to enhance job satisfaction and organizational commitment. This study contributes to the existing body of knowledge on employee satisfaction and emphasizes the importance of organizational factors in promoting a fulfilling work experience. Highlights: The study examines the impact of organizational factors on job satisfaction through the lens of organizational culture, leadership style, and work environment. Path analysis is used as the analytical tool to understand the direct and indirect effects of these factors on job satisfaction. The findings emphasize the significance of fostering a positive organizational culture, effective leadership, and a conducive work environment to enhance job satisfaction and organizational commitment. Keywords: Organizational Culture, Leadership Style, Work Environment, Job Satisfaction, Organizational Commitment.